Effect of magnetic field on thermo-physical and hydrodynamic properties of different metals-decorated multi-walled carbon nanotubes-based water coolants in a closed conduit - Shanbedi, Mehdi; Amiri, Ahmad; Zeinali Heris, Saeed; Eshghi, Hossein; Yarmand, Hooman (Springer Verlag, 2018)
In this paper, the thermo-physical and hydrodynamic properties of heat transfer nanofluids containing metal nanoparticles-decorated multi-wall carbon nanotube (MWCNT) are reported. To this end, Cu-decorated MWCNT, Fe-decorated MWCNT, and Ni-decorated MWCNT (covalently functionalized samples) were synthesized with pre-functionalization with the aspartic acid as the hydrophilic chain. To have a comprehensive comparison, water-based non-covalently functionalized MWCNT nanofluids were also synthesized. A significant increase in the thermal and electrical conductivities of heat transfer nanofluids containing metal nanoparticles-based MWCNT as compared to the non-covalently functionalized sample as well as water has been determined at the same operational conditions. All the prepared nanofluids are stable and the viscosity and density remained approximately the same after loading additives. The present paper also focused on the study of the role of weight concentrations of additives, flow rate and thermo-physical properties of the prepared nanofluids on the convective heat transfer rate and hydrodynamic performances in the laminar flow. Further, the convective heat transfer coefficient, pressure drop, friction factor, performance index and pumping power variation were also investigated under applied magnetic field, which improves the overall thermal performance of the closed conduit insignificantly.